Public governance of regional development in the context of digital transformation: theoretical and conceptual foundations - Kolinko , Mykyta (Theory and Practice of Public Administration, 2026)
The article provides a theoretical and conceptual analysis of public governance of regional development in the context of digital transformation. The relevance of the study is determined by the fact that digital technologies are changing not only the technical tools of administrative activity, but also the logic of interaction between public authorities, local self-government bodies, business and civil society. The study examines the content of the concepts of “public governance”, “regional development” and “digital transformation” and analyses scientific and regulatory approaches to their interpretation. Public governance is understood as a system of interaction between public institutions and social actors aimed at implementing the public interest. Regional development is considered not only as a process of positive changes in a region, but also as a managed evolution of a regional system from its current state to a qualitatively new one that corresponds to the strategic priorities of both the region and the state as a whole. Particular attention is paid to digital transformation as an interdisciplinary phenomenon that has specific accents in different spheres of social life, but is generally associated with the comprehensive restructuring of processes under the influence of digital technologies. The article substantiates the expediency of applying a value-result approach, which makes it possible to consider digital transformation not as an end in itself, but as a tool for achieving socially significant results: increasing the effectiveness of public governance, transparency, accessibility of public services, reducing interregional disparities and improving the quality of life of the population. Based on the generalization of the research results, the author proposes a definition of public governance of regional development in the context of digital transformation as a scientifically grounded, technologically supported and socially oriented activity of public actors aimed at strategic planning, coordination and implementation of regional policy in the space of digital social relations.